Empowering Mathematical Problem Solving in Elementary Classrooms: Challenges and Opportunities in Society 5.0 - Eliva Sukma Cipta; Nurainiyah Nurainiyah; Neneng Sulastri; Usep Suherman; Dick Dick Maulana (UIN Siber Syekh Nurjati Cirebon, 2025)
AbstractThe Society 5.0 era demands the world of education to equip students with critical, creative, and solution-oriented thinking skills in dealing with real problems. This study aims to explore the level of elementary school students' mathematical problem-solving abilities and identify the challenges and opportunities faced by teachers in building these skills in the Society 5.0 era. This study uses a mixed method approach with a sequential explanatory model. Quantitative data were obtained through problem-solving tests given to 60 fifth-grade students from two public elementary schools in Bandung Regency who were selected using stratified random sampling. The results showed that students' problem-solving abilities were in the moderate category (average = 21.6 out of a maximum score of 32), with the highest performance at the